Neuropeptide Y as a Biomarker and Therapeutic Target for Neuroblastoma - Galli, Susana (Am J Pathol, 2016)
Neuroblastoma (NB) is a pediatric malignant neoplasm of sympathoadrenal origin. Challenges in its management include stratification of this heterogeneous disease and a lack of both adequate treatments for high-risk patients and noninvasive biomarkers of disease progression. Our previous studies have identified neuropeptide Y (NPY), a sympathetic neurotransmitter expressed in NB, as a potential therapeutic target for these tumors by virtue of its Y5 receptor (Y5R)–mediated chemoresistance and Y2 receptor (Y2R)–mediated proliferative and angiogenic activities. The goal of this study was to determine the clinical relevance and utility of these findings. Expression of NPY and its receptors was evaluated in corresponding samples of tumor RNA, tissues, and sera from 87 patients with neuroblastic tumors and in tumor tissues from the TH-MYCN NB mouse model. Elevated serum NPY levels correlated with an adverse clinical presentation, poor survival, metastasis, and relapse, whereas strong Y5R immunoreactivity was a marker of angioinvasive tumor cells. In NB tissues from TH-MYCN mice, high immunoreactivity of both NPY and Y5R marked angioinvasive NB cells. Y2R was uniformly expressed in undifferentiated tumor cells, which supports its previously reported role in NB cell proliferation. Our findings validate NPY as a therapeutic target for advanced NB and implicate the NPY/Y5R axis in disease dissemination. The correlation between elevated systemic NPY and NB progression identifies serum NPY as a novel NB biomarker.